Soldering flux capable of enhancing radiation resistance of aluminum alloy brazing welding spots and preparation method and application of soldering flux
By using a new type of crickets equipped with epoxy resin and high-temperature flame-retardant resin in aluminum alloy welding, forming a "plastic-vitreous" protective layer cured at high temperature solves the existing technology in the existing technology The problem of insufficient anti -radiation capacity of welding joints has significantly improved the shear strength of the welding joints and meets the needs of the aerospace field.
Patent Information
- Application Number
- CN202411618495.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The prior art is difficult to effectively enhance the radiation resistance of the solder joints in aluminum alloy brazing, and traditional fluxes cause the shear strength of the solder joints to decrease in the high radiation environment, affecting product manufacturing in the aerospace field.
The organic mixture and balance with a new type of pyrine with a proportion of 5 % to 18 % are inorganic mixtures. Among them, organic mixtures include EP-12 epoxy resin, EP-16 epoxy resin, high-temperature flame-retardant thermal solid phenolic phenolic phenolic phenolic phenolic phenolic formation Resin and phenylbenol, combined with inorganic substances such as CSF, ALF3, GAF3, and Al (OH) 3, forming a "plastic-vitreous" protective layer solidified at high temperatures, with anti-radiation capabilities.
In a high -radiation environment, the pyrine can significantly improve the shear strength of aluminum alloy welding welded welding, meet the needs of the aerospace field, and the ductal residue does not need to be cleaned to avoid the risk of corrosion.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of brazing materials, and relates to a brazing flux capable of enhancing the radiation resistance of aluminum alloy brazing points, and a preparation method and application thereof. Background Art
[0002] As we all know, during brazing, the metal material that connects the parent metal to be welded is called brazing filler metal. However, in most cases, the brazing filler metal must be assisted by a brazing flux to achieve a reliable brazing connection. Therefore, the brazing flux is one of the important auxiliary materials in the brazing process. Generally, after the brazing flux is used to complete the brazing connection, the flux residue needs to be cleaned up by appropriate methods to prevent the residue from corroding the brazing joint metal or the parent metal or causing other adverse effects.
[0003] In recent years, there have been many inventions about Nocolok brazing fluxes used in brazing aluminum and aluminum alloys, such as K3AlF6 brazing flux, KAlF4 brazing flux or their improved brazing fluxes such as CsF-AlF3 brazing flux, and they have been widely used in the brazing connection of the same or different materials of aluminum alloy + aluminum alloy, aluminum alloy + copper alloy.
[0004] With the widespread adoption of aluminum alloy structural parts in the aerospace field, brazing technology is also playing an increasingly important role. For related special uses such as aluminum alloy antennas and waveguide devices in spacecraft, brazing joints need to have a certain radiation resistance, which can only be achieved by changing the brazing structure or physical reinforcement. However, these methods will greatly increase costs and weight, seriously affecting the development of the aerospace industry. Therefore, there is an urgent need to develop a new type of brazing flux that can enhance the radiation resistance of aluminum alloy brazing joints.
[0005] After searching, it was found that Chinese patent application CN115922150A discloses a new type of brazing flux that can enhance the radiation resistance and low temperature resistance of solder joints. The brazing flux is matched with BAg40CuZnCdNi solder and is used for brazing connections of the same or different materials of Q345 steel and 304 stainless steel, or matched with BCu80SnPAg solder and is used for brazing connections of the same or different materials of red copper and brass. Since the inorganic mixture in the above brazing flux is 4% to 13% KBF4, 5% to 12% KF, 5% to 10% Bi2O3 and the balance is B2O3, the brazing flux based on "boride" is generally not suitable for brazing of aluminum alloys. Therefore, it is necessary to find another way to develop a new type of brazing flux that can enhance the radiation resistance of aluminum alloy brazing joints to meet the needs of product manufacturing in the aerospace field. Summary of the invention
[0006] The purpose of the present invention is to provide a flux that can enhance the radiation resistance of aluminum alloy brazing points, and a preparation method and application thereof. The residue after brazing with the flux can form a dense, thin and uniform "plastic-glass" protective layer with radiation resistance, which can meet the needs of aerospace devices such as aluminum alloy antennas, aluminum alloy waveguide devices and other brazing points.
[0007] The technical solution for achieving the purpose of the present invention is as follows:
[0008] The invention discloses a brazing flux capable of enhancing the radiation resistance of aluminum alloy brazing points. The brazing flux comprises 5% to 18% of an organic mixture and the remainder of an inorganic mixture in terms of mass percentage. The organic mixture comprises 7% to 15% of EP-12 epoxy resin, 8% to 16% of EP-16 epoxy resin, 5% to 8% of F-51A high temperature flame retardant thermosetting phenolic resin, 5% to 8% of F-52A high temperature flame retardant thermosetting phenolic resin, 5% to 8% of resorcinol, 5% to 8% of hydroquinone, and the remainder of phthalic anhydride. The inorganic mixture comprises 40% to 55% of CsF, 20% to 30% of AlF3, 0.005% to 0.01% of GaF3, and the remainder of Al(OH)3 in terms of mass percentage.
[0009] The method for preparing the brazing flux capable of enhancing the radiation resistance of aluminum alloy brazing points comprises the following steps:
[0010] (1) EP-12 epoxy resin, EP-16 epoxy resin, F-51A high temperature flame retardant thermosetting phenolic resin, F-52A high temperature flame retardant thermosetting phenolic resin, resorcinol, hydroquinone, and phthalic anhydride are uniformly mixed in a stainless steel container according to a proportion to obtain an organic mixture;
[0011] (2) mixing CsF, AlF3, GaF3, and Al(OH)3 in a stainless steel container in a uniform ratio to obtain an inorganic mixture;
[0012] (3) The organic mixture and the inorganic mixture are uniformly mixed in a stainless steel container according to a proportion to obtain a flux.
[0013] Preferably, in the above preparation method, the purity of each raw material used is greater than 99.5%.
[0014] Furthermore, the present invention also provides an application of the above-mentioned brazing flux, and the specific application method is: matching the above-mentioned brazing flux with Zn-Al brazing filler metal for brazing connection of the same material or different materials such as aluminum alloy + aluminum alloy, aluminum alloy + copper alloy.
[0015] Unlike the brazing method of the brazing flux reported in Chinese patent application CN115922150A, which is limited to the induction brazing process, the brazing flux obtained by the present invention can be applied to a variety of brazing processes such as furnace brazing, flame brazing, induction brazing, etc. After brazing, the flux residue forms a dense, thin and uniform "plastic-glass" protective layer on the surface of the solder joint and has radiation resistance. In addition, the shear strength of the brazed solder joint can be increased by more than 15% compared with the shear strength of the brazed solder joint using the existing commercially available CsF-AlF3 flux, meeting the urgent needs of product manufacturing in the aerospace field. DETAILED DESCRIPTION
[0016] Compared with the traditional Nocolok brazing flux such as K3AlF6 brazing flux, KAlF4 brazing flux and CsF-AlF3 brazing flux, the technical solution adopted by the present invention creatively solves the following key technical problems:
[0017] 1) K3AlF6 and KAlF4 fluxes are not suitable for brazing of aluminum alloy + copper alloy, while CsF-AlF3 flux, which is an "improved" Nocolok flux, is the best choice for brazing of aluminum alloy + copper alloy. Similarly, the traditional CsF-AlF3 flux is mainly used to react with the oxides on the surface of the base material and the solder at the selected brazing temperature, so as to remove the oxide film and clean the base material and the solder surface, thereby facilitating the wetting, spreading and filling of the liquid solder. Although the CsF-AlF3 flux residue is less corrosive, in most cases, the flux residue still needs to be cleaned after brazing. Based on the special performance of the brazing flux of the present invention and in order to meet the requirement that many brazing seams of aluminum alloy structures cannot be cleaned, it is necessary to enable the brazing flux residue after brazing to be organically combined with the "organic mixture" to form a thin and dense "plastic-glass" layer. Therefore, in addition to considering that the organic mixture combination cannot cause a negative effect on the brazing flux formula (i.e., the inorganic mixture) when adding "epoxy resin + phenolic resin", the selection and combination of resins must also meet the requirements of high temperature resistance and a higher curing temperature (600°C to 700°C).
[0018] After a lot of exploration and experiments, it was found that by selecting EP-12 epoxy resin and EP-16 epoxy resin with good radiation resistance, matching them with a new resin combination of F-51A high-temperature resistant flame retardant thermosetting phenolic resin and F-52A high-temperature resistant flame retardant thermosetting phenolic resin, and using resorcinol, hydroquinone and phthalic anhydride as curing agent and accelerator respectively, the organic mixture can be smoothly cured when brazing is heated at 600℃~700℃ and form a thin and uniform plastic-glass body together with the CsF-AlF3 flux residue and can be evenly covered on the surface of the aluminum alloy brazing joint, so that the aluminum alloy brazing joint has good radiation resistance and can also significantly improve the shear strength of the brazing joint.
[0019] 2) The main components of the traditional cesium-containing Nocolok aluminum alloy brazing flux (such as CsF-AlF3 brazing flux) are CsAlF4, CsF, and AlF3. It can effectively protect the base material from oxidation and promote the flow of brazing filler metal when brazing aluminum alloy + aluminum alloy, aluminum alloy + copper alloy in the range of 500-700℃ with Zn-Al brazing filler metal. However, the aluminum alloy brazing joints formed do not have radiation resistance. Experiments show that: 60 Under the condition of Co-γ radiation source radiation dose rate of 0.25Gy(Si) / s, after irradiation for 720 hours, the shear strength of the brazed joint decreased by more than 20%.
[0020] The traditional CsF-AlF3 flux, whose disclosed components are mainly CsAlF4, is generally mixed directly with CsF and AlF3 in a molar ratio of 1:1. Since the F ion content in the CsAlF4 flux is as high as 32%, the residue left after brazing is basically in the form of slag powder. How to make the traditional CsAlF4 flux have a good film removal ability, and its residue can form a thin and dense "glass body" and organically combine with the "epoxy resin + phenolic resin" organic mixture to form a "plastic-glass body", it is necessary to improve and optimize its components. To this end, the inventors have obtained a new inorganic combination of CsF, AlF3, GaF3, and Al(OH)3 that meets the above requirements after a large number of exploratory tests, component optimization, and content optimization. The key to this combination is that CsF and AlF3 fluorides are greatly reduced, and Al(OH)3 is increased by about 20% (because Al(OH)3 will form Al2O3, which is easy to form transparent alumina ceramics after high temperature heating). This novel combination allows the residue after brazing to form a thin and dense plastic-glass body + alumina ceramic, and the residue is basically non-corrosive and does not require cleaning.
[0021] It should be emphasized that the organic mixture ratio reported in CN115922150A is not compatible with the inorganic mixture of the present invention, that is, it is easy to cause delamination and hardening, and it is impossible to prepare a brazing flux with uniform texture and excellent brazing performance. Therefore, it is necessary to optimize the components and contents of epoxy resin, curing agent and accelerator to solve the delamination and hardening problems that may occur in the new brazing flux.
[0022] The flux-matched Zn-Al solder obtained by uniformly mixing the preferred and optimized organic mixture with the inorganic mixture of the present invention can be used for brazing connection of the same material or different materials such as aluminum alloy + aluminum alloy and aluminum alloy + copper alloy.
[0023] The brazing flux of the present invention can be matched with Zn-Al brazing filler metal to braze aluminum alloy + aluminum alloy, aluminum alloy + copper alloy in a heating range of 600° C. to 700° C. under various brazing process conditions such as furnace brazing, flame brazing, induction brazing, etc., to obtain brazing points with excellent radiation resistance, and the shear strength of the brazing points can be increased by more than 10% compared with the shear strength of the brazing points obtained by using the commercially available CsAlF4 brazing flux.
[0024] The present invention is further described in detail below in conjunction with specific embodiments.
[0025] Example 1
[0026] The flux can enhance the radiation resistance of aluminum alloy brazing points. The mass percentage ratio is: 5% organic mixture, the balance is inorganic mixture; the mass percentage ratio of the organic mixture is: 7% EP-12 epoxy resin, 16% EP-16 epoxy resin, 5% F-51A high temperature flame retardant thermosetting phenolic resin, 8% F-52A high temperature flame retardant thermosetting phenolic resin, 5% resorcinol, 8% hydroquinone, the balance is phthalic anhydride; the mass percentage ratio of the inorganic mixture is: 40% CsF, 30% AlF3, 0.005% GaF3, the balance is Al(OH)3. The flux is prepared by the following steps:
[0027] (1) EP-12 epoxy resin, EP-16 epoxy resin, F-51A high temperature flame retardant thermosetting phenolic resin, F-52A high temperature flame retardant thermosetting phenolic resin, resorcinol, hydroquinone, and phthalic anhydride are uniformly mixed in a stainless steel container according to a proportion to obtain an organic mixture;
[0028] (2) mixing CsF, AlF3, GaF3, and Al(OH)3 in a stainless steel container in a uniform ratio to obtain an inorganic mixture;
[0029] (3) The organic mixture and the inorganic mixture are uniformly mixed in a stainless steel container according to a proportion to obtain a flux.
[0030] The above-mentioned brazing flux is matched with Zn85-Al15 brazing filler metal, and 6063 aluminum alloy + 6063 aluminum alloy (plate thickness 3mm, overlap width 5mm, the same below) are brazed in the form of lap joint using furnace heating, and the shear strength of the brazed joint (all data are the average of 5 experimental data, the same below) is 135±10MPa (broken at the brazing seam). The above-mentioned brazing flux is matched with Zn85-Al15 brazing filler metal to braze 6063 aluminum alloy + H58 copper alloy (plate thickness 3mm, overlap width 5mm, the same below), and the shear strength of the brazed joint (all data are the average of 5 experimental data, the same below) is 135±10MPa (broken at the brazing seam).
[0031] Brazed joint specimens 60 Under the condition of 0.25Gy(Si) / s radiation dose rate of Co-γ radiation source, after 720 hours of radiation, the shear strength of 6063 aluminum alloy + 6063 aluminum alloy brazed joint decreased slightly to 130±10MPa (broken at the brazing seam). The shear strength of 6063 aluminum alloy + H58 copper alloy brazed joint remained basically unchanged, with a shear strength of 133±10MPa (broken at the brazing seam).
[0032] Example 2
[0033] The flux capable of enhancing the radiation resistance of aluminum alloy brazing points is composed of 18% organic mixture and the balance inorganic mixture in terms of mass percentage; the organic mixture is composed of 15% EP-12 epoxy resin, 8% EP-16 epoxy resin, 8% F-51A high temperature flame retardant thermosetting phenolic resin, 5% F-52A high temperature flame retardant thermosetting phenolic resin, 8% resorcinol, 5% hydroquinone, and the balance is phthalic anhydride; the inorganic mixture is composed of 55% CsF, 20% AlF3, 0.01% GaF3, and the balance is Al(OH)3 in terms of mass percentage. The preparation method is the same as that of Example 1.
[0034] The above-mentioned brazing flux is matched with Zn85-Al15 brazing filler metal, and 6063 aluminum alloy + 6063 aluminum alloy (plate thickness 3mm, overlap width 5mm, the same below) are brazed by induction heating in the form of lap joint, and the shear strength of the brazed joint (all data are the average of 5 experimental data, the same below) is 135±10MPa (broken at the brazing seam). The above-mentioned brazing flux is matched with Zn85-Al15 brazing filler metal to braze 6063 aluminum alloy + H58 copper alloy (plate thickness 3mm, overlap width 5mm, the same below), and the shear strength of the brazed joint (all data are the average of 5 experimental data, the same below) is 135±10MPa (broken at the brazing seam).
[0035] Brazed joint specimens 60 Under the condition of 0.25Gy(Si) / s radiation dose rate of Co-γ radiation source, after 720 hours of radiation, the shear strength of 6063 aluminum alloy + 6063 aluminum alloy brazed joint decreased slightly to 130±10MPa (broken at the brazing seam). The shear strength of 6063 aluminum alloy + H58 copper alloy brazed joint remained basically unchanged, with a shear strength of 133±10MPa (broken at the brazing seam).
[0036] Example 3
[0037] The flux capable of enhancing the radiation resistance of aluminum alloy brazing points is composed of 12% organic mixture and the balance inorganic mixture in terms of mass percentage; the organic mixture is composed of 11% EP-12 epoxy resin, 12% EP-16 epoxy resin, 6.5% F-51A high temperature flame retardant thermosetting phenolic resin, 7% F-52A high temperature flame retardant thermosetting phenolic resin, 7% resorcinol, 6% hydroquinone, and the balance is phthalic anhydride; the inorganic mixture is composed of 50% CsF, 25% AlF3, 0.008% GaF3, and the balance is Al(OH)3 in terms of mass percentage. The preparation method is the same as that of Example 1.
[0038] The above-mentioned brazing flux is matched with Zn85-Al15 brazing filler metal, and 6063 aluminum alloy + 6063 aluminum alloy (plate thickness 3mm, overlap width 5mm, the same below) are brazed in the form of lap joint using propane flame heating, and the shear strength of the brazed joint (all data are the average of 5 experimental data, the same below) is 135±10MPa (broken at the brazing seam). The above-mentioned brazing flux is matched with Zn85-Al15 brazing filler metal to braze 6063 aluminum alloy + H58 copper alloy (plate thickness 3mm, overlap width 5mm, the same below), and the shear strength of the brazed joint (all data are the average of 5 experimental data, the same below) is 135±10MPa (broken at the brazing seam).
[0039] Brazed joint specimens 60 Under the condition of 0.25Gy(Si) / s radiation dose rate of Co-γ radiation source, after 720 hours of radiation, the shear strength of 6063 aluminum alloy + 6063 aluminum alloy brazed joint decreased slightly to 130±10MPa (broken at the brazing seam). The shear strength of 6063 aluminum alloy + H58 copper alloy brazed joint remained basically unchanged, with a shear strength of 133±10MPa (broken at the brazing seam).
[0040] Comparative Example 1
[0041] The commercially available CsF-AlF3 brazing flux was matched with the Zn85-Al15 brazing filler metal, and the brazing flux was matched with the Zn85-Al15 brazing filler metal in the form of a lap joint. The 6063 aluminum alloy + 6063 aluminum alloy (plate thickness 3 mm, lap width 5 mm, the same below) was brazed using induction heating in the form of a lap joint, and the shear strength of the brazed joint (all data are the average of 5 experimental data, the same below) was 110±10MPa (broken at the brazing seam). The brazing flux was matched with the Zn85-Al15 brazing filler metal to braze 6063 aluminum alloy + H58 copper alloy (plate thickness 3 mm, lap width 5 mm, the same below), and the shear strength of the brazed joint (all data are the average of 5 experimental data, the same below) was 110±10MPa (broken at the brazing seam).
[0042] Brazed joint specimens 60 Under the condition of 0.25Gy(Si) / s radiation dose rate of Co-γ radiation source, after 720 hours of radiation, the shear strength of 6063 aluminum alloy + 6063 aluminum alloy brazed joint decreased significantly, and the average value of 5 experimental data was 85±10MPa (broken at the brazing seam). The shear strength of 6063 aluminum alloy + H58 copper alloy brazed joint also decreased significantly, and the average value of 5 experimental data was 88±10MPa (broken at the brazing seam).
[0043] Comparative Example 2
[0044] The inorganic mixture described in Example 3 is matched with a flux consisting of 50% CsF, 25% AlF3, 0.008% GaF3, and the balance Al(OH)3 in mass percentage, and the flux-matched Zn85-Al15 solder is brazed by propane flame heating in the form of a lap joint. 6063 aluminum alloy + 6063 aluminum alloy (plate thickness 3 mm, lap width 5 mm, the same below) is brazed in a lap joint by furnace heating, and the shear strength of the brazed joint (all data are the average values of 5 experimental data, the same below) is 115±10 MPa (broken at the brazing seam). The above-mentioned brazing flux is matched with Zn85-Al15 brazing filler metal to braze 6063 aluminum alloy + H58 copper alloy (plate thickness 3mm, overlap width 5mm, the same below), and the shear strength of the brazed joint (all data are the average of 5 experimental data, the same below) is 115±10MPa (broken at the brazing seam).
[0045] Brazed joint specimens 60 Under the condition of Co-γ radiation source radiation dose rate of 0.25Gy(Si) / s, after 720 hours of radiation, the shear strength of 6063 aluminum alloy + 6063 aluminum alloy brazed joint decreased significantly, and the average value of 5 experimental data was 90±10MPa (broken at the brazing seam). The shear strength of 6063 aluminum alloy + H58 copper alloy brazed joint also decreased significantly, and the average value of 5 experimental data was 92±10MPa (broken at the brazing seam).
[0046] Comparative Example 3
[0047] 82.5% of the inorganic mixture described in Example 3 (the specific ratio of the inorganic mixture is: 50% CsF, 25% AlF3, 0.008% GaF3, and the balance is Al(OH)3) and 17.5% of the organic mixture described in Example 3 reported in CN115922150A (the specific ratio of the organic mixture is: 20% E-51 epoxy resin, 15% F-51B high temperature flame retardant thermosetting phenolic resin, 15% F-52B high temperature flame retardant thermosetting phenolic resin, 13% resorcinol, and the balance is phthalic anhydride) are mixed in a stainless steel container for 10-20 minutes. The resulting flux is similar to a "porridge-like" mixture and cannot form a mixture with a uniform texture.
[0048] The brazing flux is matched with Zn85-Al15 brazing filler metal. Before brazing, the brazing flux is stirred again with an experimental stirrer for 5-10 minutes, and the brazing is performed by oxypropane flame heating in the form of a lap joint. The brazing flux is matched with Zn85-Al15 brazing filler metal, and 6063 aluminum alloy + 6063 aluminum alloy (plate thickness 3mm, lap width 5mm, the same below) are brazed in a furnace in the form of a lap joint. The shear strength of the brazed joint (all data are the average of 5 experimental data, the same below) is 75±10MPa (broken at the brazing seam). The brazing flux is matched with Zn85-Al15 brazing filler metal to braze 6063 aluminum alloy + H58 copper alloy (plate thickness 3mm, lap width 5mm, the same below), and the shear strength of the brazed joint (all data are the average of 5 experimental data, the same below) is 65±10MPa (broken at the brazing seam), which is significantly lower than the shear strength of the brazed joint in the embodiment.
[0049] After irradiation for 720 hours under the condition of 60Co-γ radiation source with a radiation dose rate of 0.25Gy(Si) / s, the shear strength of the 6063 aluminum alloy + 6063 aluminum alloy brazed joint decreased significantly, and the average value of 5 experimental data was 40±10MPa (broken at the brazing seam). The shear strength of the 6063 aluminum alloy + H58 copper alloy brazed joint also decreased significantly, and the average value of 5 experimental data was 30±10MPa (broken at the brazing seam), which was significantly lower than the shear strength of the brazed joint in the embodiment.
[0050] It can be seen from the test data of Examples 1 to 3 that the brazing flux of the present invention is matched with the Zn85-Al15 brazing filler metal, and the brazed joints obtained by brazing 6063 aluminum alloy + 6063 aluminum alloy and 6063 aluminum alloy + H58 copper alloy by furnace heating, flame heating, or induction heating are 60After irradiation for 720 hours at a Co-γ radiation source with a radiation dose rate of 0.25 Gy (Si) / s, the shear strength of the 6063 aluminum alloy + 6063 aluminum alloy brazing joint only slightly decreased, while the shear strength of the 6063 aluminum alloy + H58 copper alloy brazing joint remained almost unchanged, indicating that the brazing flux and its brazing flux residue of the present invention have significant radiation resistance.
[0051] By comparing the three embodiments with the three comparative examples, it can be seen that the shear strength of the aluminum alloy + aluminum alloy or aluminum alloy + copper alloy brazing joint obtained by using the brazing flux of the present invention and the Zn85-Al15 brazing filler metal is significantly improved (increased by about 18%) than that of the aluminum alloy + aluminum alloy or aluminum alloy + copper alloy brazing joint obtained by using the brazing flux of the present invention and the Zn85-Al15 brazing filler metal as commercially available CsF-AlF3 brazing flux or the brazing flux composed of the inorganic mixture described in Example 3 and the Zn85-Al15 brazing filler metal as described in Example 3. 60 Under the condition of the radiation dose rate of the Co-γ radiation source of 0.25Gy(Si) / s, after 720 hours of radiation, the shear strength of the brazed joint decreased significantly (by about 20%). Comparative Example 3 Since the organic mixture and the inorganic mixture cannot be organically matched, the soldering performance is extremely poor. Although the brazing material remains unchanged and is a brazing material particularly suitable for aluminum alloy + aluminum alloy or aluminum alloy + copper alloy brazing, the shear strength of the obtained brazed joint is only about 50% of that of the embodiment; 60 Under the condition of 0.25Gy(Si) / s radiation dose rate of Co-γ radiation source, the shear strength of brazed joint decreased by more than 45% after 720 hours of radiation. This is because the flux residue is unevenly distributed on the brazed joint, and therefore, it has almost no anti-radiation effect.
[0052] Comparison with Comparative Examples 1 to 2 shows that the technical solution of the present invention can not only enhance the radiation resistance of aluminum alloy brazing points, but also significantly improve the shear strength of brazed joints; comparison with Comparative Example 3 shows that in different inorganic mixture systems, the addition of organic mixtures such as epoxy resin systems requires "specific analysis of specific circumstances", and the components and composition of the resin, curing agent, and accelerator must be reasonably selected, and the amount of addition also needs to be reasonably adjusted.
Claims
1. A flux capable of enhancing the radiation resistance of aluminum alloy brazing points, characterized in that: The mass percentage ratio is: 5% to 18% of the organic mixture, and the balance is the inorganic mixture; the mass percentage ratio of the organic mixture is: 7% to 15% of EP-12 epoxy resin, 8% to 16% of EP-16 epoxy resin, 5% to 8% of F-51A high temperature resistant flame retardant thermosetting phenolic resin, 5% to 8% of F-52A high temperature resistant flame retardant thermosetting phenolic resin, 5% to 8% of resorcinol, 5% to 8% of hydroquinone, and the balance is phthalic anhydride; the mass percentage ratio of the inorganic mixture is: 40% to 55% of CsF, 20% to 30% of AlF3, 0.005% to 0.01% of GaF3, and the balance is Al(OH)3.
2. The method for preparing the flux according to claim 1, characterized in that: The following steps are involved: (1) EP-12 epoxy resin, EP-16 epoxy resin, F-51A high temperature flame retardant thermosetting phenolic resin, F-52A high temperature flame retardant thermosetting phenolic resin, resorcinol, hydroquinone, and phthalic anhydride are uniformly mixed in a stainless steel container according to a proportion to obtain an organic mixture; (2) CsF, AlF3, GaF3, and Al(OH)3 are uniformly mixed in a stainless steel container according to a ratio to obtain an inorganic mixture; (3) The organic mixture and the inorganic mixture are mixed uniformly in a stainless steel container according to the proportions to obtain a flux.
3. The preparation method according to claim 2, characterized in that: The purity of each raw material is greater than 99.5%.
4. The use of the flux according to claim 1, characterized in that: The specific application method is: matching the brazing flux described in claim 1 with Zn-Al brazing filler metal for brazing connection of the same material or different materials such as aluminum alloy + aluminum alloy, aluminum alloy + copper alloy.
5. The use according to claim 4, characterized in that: The brazing process is selected from furnace brazing, flame brazing or induction brazing.
Citation Information
Patent Citations
Ecological ammunition
CN103781930A
Cesium-rubidium brazing flux used for brazing aluminum steel and aluminum bronze
CN103934595A
High-heat-conductivity epoxy resin conducting resin and preparing method thereof
CN105315943A
Methods and compositions for forming solder bumps on a substrate with radiation curable or thermal curable solder flux
CN106134300A
Epoxy resin composite Sn-Bi lead-free soldering paste
CN109175771A